Examining the Possibility of Detecting Brucella Canis from Tissue Samples Using Bruce-Ladder Multiplex PCR Assay - Stević Nataša (Sciendo, 2017)
The goal of this study was to compare the results of serological and conventional bacteriological methods with the results obtained using multiplex PCR Bruce-ladder assay. Based on the obtained results, the usability of the assay was assessed in regard to rapid diagnosis of canine brucellosis directly from the samples of reproductive organs of infected dogs. Out of 225 blood samples, 33 (14.67%) had a positive agglutination reaction. In this study, out of the 225 assayed reproductive organs of dogs, B. canis was isolated from 3 samples (1.33%), while the PCR Bruce-ladder assay detected two positive samples (0.88%). Two dogs from which B. canis was isolated, an antibody titer of 1/200 was established in blood serums, and third dog from which B. canis was isolated was negative using the tube agglutination test. From a total of 225 assayed organ samples, a positive PCR reaction was obtained from two samples. The obtained results show that the tube agglutination method remains the first choice for the detection of dogs infected with B. canis. In addition, whenever possible, it is necessary to try isolation. It is desirable to attempt the detection of B. canis in tissues using PCR, but the results may not be treated as definitive and reliable.